Efectividad del tratamiento restaurativo atraumático en la remoción de caries en pacientes pediátricos en edades escolares. revisión bibliográfica - Flores Portugal, Edison Xavier (2024)
Introduction: Caries is a multifactorial infectious disease and it is recognized that it affects general health and quality of life. Therefore, its most commonly used treatment is the removal of carious tissue, however, this procedure can generate problems of fear and anxiety, which has led to the use of minimally invasive techniques. Objective: To identify the effectiveness of atraumatic restorative treatment in the survival of caries restorations in primary and permanent dentition in pediatric patients of school age through a literature review and thus provide information on the advantages and disadvantages of this restorative technique. Method: Qualitative approach, descriptive and analytical type of research with a bibliographic method of scientific articles obtained from PubMed, ScienceDirect and LILACS databases using advanced search strings. Results: A total of 117 scientific articles were collected, of which only 12 were selected after a discarding process. TRA does not require a long application time, which generates less discomfort favoring the reduction of anxiety and adverse effects. Conclusions: Atraumatic restorative treatment (ART), being a minimally invasive technique that uses hand instruments to selectively remove carious tissue, has a survival rate of restorations that varies between 47% and 90% in primary and permanent dentition in pediatric patients of school age.